History and theory in anthropology - Barnard, Alan (Alan J.) (Cambridge, United Kingdom ; New York, NY : Cambridge University Press, 2022)
"In the past twenty years, there have been exciting new developments in the field of anthropology. This second edition of Barnard's classic textbook on the history and theory of anthropology has been revised and expanded to include up-to-date coverage on all the most important topics in the field. Its coverage ranges from traditional topics like the beginnings of the subject, evolutionism, functionalism, structuralism, and Marxism, to ideas about globalization, post-colonialism, and notions of 'race' and of being 'indigenous'. There are several new chapters, along with an extensive glossary, index, dates of birth and death, and award-winning diagrams. Although anthropology is often dominated by trends in Europe and North America, this edition makes plain the contributions of trendsetters in the rest of the world too. With its comprehensive yet clear coverage of concepts, this is essential reading for a new generation of anthropology students"--
List of figures -- List of tables -- Preface -- Visions of anthropology -- Precursors -- Changing perspectives on evolution -- Diffusionist and culture area theories -- Functionalism and structural-functionalism -- Action and process -- Marxist perspectives -- From relativism to cognitive science -- Structuralism, from linguistics to anthropology -- Poststructuralists and feminists -- Mavericks -- Interpretive approaches -- Postmodernism and Its aftermath -- Conclusions -- Appendix 1: dates of birth and death -- Appendix 2: glossary.
Includes bibliographical references and index.
Keywords: Anthropology -- Philosophy; Anthropology -- History; SOCIAL SCIENCE / Anthropology / General